The Effect of Work Environment on Employee Loyalty with Work Stress as an Intervening Variable at Bella Vita Hotel - Kota Kupang - Zet Ena; Alya Elita Sjioen; Ayub M. Riwudjami (Quantitative Economics and Management Studies, 2022)
The purpose of this study was to see how the work environment, work stress, and employee loyalty and how the relationship between these three variables at Bella Vita Hotel Kupang, because the researchers found that there was an increase in the level of employee absenteeism when the number of positive confirmed cases of covid-19 in Kupang City more and more. This study uses the Spearman rank correlation test analysis technique. It is known that the work environment has a positive relationship with employee loyalty as indicated by a sig(2-tailed) value of 0.041 and a correlation coefficient of 0.462 which means the better the work environment, the higher the employee loyalty, and on the contrary. Job stress has a negative relationship with employee loyalty as indicated by a sig(2-tailed) value of 0.042 and a correlation coefficient of -0.459 which means the higher the work stress, the lower the employee loyalty, and vice versa. While the work environment has no relationship with work stress, because based on the results of the correlation test, the value of sig(2-tailed) is 0.878 where this value is greater than 0.05.